The Significance of the Style of Thinking in Scientific Knowledge (Texas Journal of Engineering and Technology, 2023)
This article reveals the significance of the way of thinking in the process of perception and knowledge of the world, together with the philosophical and methodological aspects, in scientific knowledge. Also, in the evolution of thinking, specific aspects of the dialectics of language and consciousness are distinguished.